THE ROLE OF PRAGMATIC AWARENESS IN EFL UNIVERSITY STUDENTS' COMMUNICATION SKILLS - Humayrah, Ulysa; Siregar, Deasy Yunita; Hajmi, Muhammad Faisal; Nasution, M. Habib Rifki; Hsb, Juanda Muktar; Fadillah, Faris; Ridwan, Achmad (UIN Sumatera Utara, 2024)
This study investigates the relationship between pragmatic awareness and communication skills among EFL university students. Using a mixed-methods approach, 150 students from one of university in Medan participated in a 4-week study involving pragmatic awareness tests, communication skills assessments, semi-structured interviews, and classroom observations. Results revealed a strong positive correlation between pragmatic awareness and overall communication abilities. Students who received explicit pragmatic instruction demonstrated significant improvements in both pragmatic competence and communication skills compared to the control group. Qualitative data highlighted enhanced cultural sensitivity, improved interpretation of implicit meanings, and increased adaptability as key benefits of pragmatic awareness. The study concludes that integrating pragmatic instruction into EFL curricula is crucial for developing effective communicators in diverse cultural contexts. Implications for EFL pedagogy and suggestions for future research are discussed.